Understanding Manta's Multidimensional Poverty Using Administrative Records - VIZUETE-SALAZAR , YASMINA; FLORES, MIGUEL; LOZA-AGUIRRE, EDISON (Journal of Ecohumanism, 2024)
The formulation of public policies aims to guide and direct activities at various levels of government to address situations affecting social sectors within a specific territory. To address these needs, this study proposes the development of an indicator to characterize the population of Manta using a multidimensional poverty index, consolidating data on the consumption of basic services, and accessibility to health and education services. Data analysis is crucial for supporting public sector operations and making informed decisions. This study conducts a comprehensive analysis of multidimen-sional poverty in Manta in 2019, using the multidimensional poverty index (MPI) based on the Alkire & Foster methodology, which measures depriva-tions in health, education, and living standards. The innovation of this work lies in using alternative administrative data to calculate the MPI, providing a more accurate and efficient measure for public policy decision-making aimed at poverty reduction. This study not only classifies Manta's sectors based on consumption behaviors and service accessibility but also offers an essential tool for improving the population's quality of life through effec-tive public policies based on precise data.